Histomorphological differentiation of non‐erosive reflux disease and functional heartburn in patients with PPI‐refractory heartburn. Issue 6 (29th July 2013) - Kandulski, A.; Jechorek, D.; Caro, C.; Weigt, J.; Wex, T.; Mönkemüller, K.; Malfertheiner, P.
Summary Background Proton pump inhibitor (PPI)‐refractory heartburn may be due to persistent gastro‐oesophageal reflux, oesophageal hypersensitivity or functional heartburn (FH). The differentiation between non‐erosive reflux disease (NERD) and FH may be very difficult. However, this differentiation is important for appropriate therapeutic management. Dilated intercellular spaces (DIS), papillary elongation (PE) and basal cell hyperplasia (BCH) can be all assessed by light microscopy. Whether these mucosal abnormalities allow the differentiation of NERD from FH in PPI‐refractory patients is uncertain. Aim To assess histopathological findings by light microscopy in patients with refractory heartburn to differentiate NERD from FH. Methods Sixty‐two patients with PPI‐refractory symptoms underwent EGD and MII‐pH after pausing PPI medication for 2 weeks before investigation. Twenty‐five subjects without upper gastrointestinal symptoms were included as controls. Symptom assessment was based on the reflux disease questionnaire (RDQ). Biopsies were taken 3–5 cm above the gastro‐oesophageal junction. DIS, PE, BCH and infiltration of immune cells were evaluated and a sum score was calculated. Results Based on endoscopy and MII‐pH, GERD was diagnosed in 43 patients (NERD: 20; ERD: 23) and FH in 19 patients. There was no difference in symptoms between the groups. Each individual histopathological item was different between the groups (P < 0.0001). Between NERD and FH, the most significant difference was found for DIS and the histopathological sum score (P < 0.001). Conclusions These findings suggest that oesophageal biopsies are useful to differentiate NERD from FH. Increased DIS and a histological sum score are the most significant histopathological abnormalities in NERD as compared with FH.